Transition to retirement and participation in mainstream community groups using active mentoring: a feasibility and outcomes evaluation with a matched comparison group. (11th December 2014) - Stancliffe, R. J.; Bigby, C.; Balandin, S.; Wilson, N. J.; Craig, D.
Abstract Background This paper reports on the feasibility and outcomes of a transition to retirement programme for older adults with disability. Without activities and social inclusion, retirees with disability are likely to face inactivity, isolation and loneliness. Methods Matched intervention and comparison groups each consisted of 29 older individuals with disability. There were 42 men and 16 women with a mean age of 55.6 years While attending their individual mainstream community group 1 day per week, intervention group participants received support from community group members trained as mentors. We assessed participants' loneliness, social satisfaction, depression, life events, quality of life, community participation, social contacts, and work hours before and 6 months after joining a community group. Results Twenty‐five (86%) of the intervention group attended their community group weekly for at least 6 months. They increased their community participation, made an average of four new social contacts and decreased their work hours. Intervention participants were more socially satisfied post‐intervention than comparison group members. Conclusions The results demonstrate that participation in mainstream community groups with support from trained mentors is a viable option for developing a retirement lifestyle for older individuals with disability.